Mengkaji Makna Doa “Torok Tae” Syukur Panen dalam Perayaan Ekaristi di Stasi Colol Paroki Santo Petrus Colol Keuskupan Ruteng - Petrus Yansen; Yohanes Rusae; Florens Maxi Un Bria (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the meaning of the Torok Tae prayer as an expression of thanksgiving for the harvest in the Eucharistic Celebration at Colol Outstation, Saint Peter Colol Parish, Diocese of Ruteng. Torok Tae is a traditional prayer of the Manggarai community that has been passed down through generations as an expression of gratitude to God for the harvest while reflecting respect for the values of life, communal solidarity, and the harmonious relationship between human beings, nature, and the Creator. This research employed a qualitative approach using a descriptive method. Data were collected through observation, in-depth interviews with the parish priest, traditional leaders, liturgical ministers, and parishioners, as well as documentation studies. The data were analyzed through data reduction, data presentation, and systematic conclusion drawing. The findings reveal that the Torok Tae prayer embodies religious, theological, social, cultural, and ecological values that are closely aligned with the spirituality of thanksgiving celebrated in the Eucharist. The integration of this traditional prayer into the liturgy represents a form of liturgical inculturation that enriches the faithful's participation without diminishing the essential nature of the Eucharist as the source and summit of Christian life. Furthermore, the incorporation of Torok Tae into the Eucharistic Celebration demonstrates that local cultural values can serve as an effective medium for contextual evangelization while strengthening the identity of the local Church. Therefore, this practice possesses significant pastoral relevance in fostering the faith life of the Christian community, preserving Manggarai cultural heritage, and promoting a harmonious dialogue between the Catholic faith and local culture.